Model for Development of Copra Farmer Empowerment Through Institutional Training - Yuan Fence Irala; Sucihatiningsih Dian Wisika Prajanti; Kardoyo Kardoyo (Economics Development Analysis Journal, 2020)
This study aimed to develop a model for the development of copra farmersâ€™ empowerment through institutional training for farmer business groups which process coconut derivative products in Asimiro Village, Loloda Sub-district, Halmahera Regency. The study employed Research and Development approach. Meanwhile, there were two types of data used, namely primary and secondary data. The results showed that problems faced by copra farmers in Asimiro Village were limited capital, traditional technology, and marketing strategies that still depended on collectors. There are several farmersâ€™ empowerment programs done through training and socialization conducted in Asimiro, namely: 1) program for the development of coconut and onion cultivation through the socialization from the Agricultural Technical Service of North Halmahera Regency; and 2) program for the improvement of smallholder welfare (PKPK) through training and socialization of â€œdapur sehatâ€ (healthy kitchen) conducted by the Village Community Empowerment Agency in collaboration with the Family Planning Agency. The results of expert practitioner validation for the model gained the percentage of 80.76%. Meanwhile, the academics validators gave 74.99% for the model. It shows that the model for the empowerment of copra farmers in this study can be classified into good category and valid.